Advanced Data Mining - Mick Benson (editor)
This book consists of advanced information regarding data mining and their applications. It offers to aid data miners, researchers, scholars, and PhD students who aspire to practice data mining techniques. The elementary contribution of this book is to mark frontier fields and implementations of knowledge discovery and data mining. It may appear that the same things are being repeated but in general, same approach and techniques may aid us in various fields and proficiency areas. This book reflects knowledge discovery and data mining applications that include areas of statistics, machine learning, data management and databases, pattern recognition, artificial intelligence and other areas. This book majorly focuses on several applications of data mining.